Effects of residual black wolfberry fruit on growth performance, rumen fermentation parameters, microflora and economic benefits of fattening sheep - Hou, Liangzhong; Duan, Pingping; Yang, Yuxia; Shah, Ali Mujtaba; Li, Jinlong; Xu, Congbin; Guo, Tongjun (Frontiers in Veterinary Science, 2025)
IntroductionThe residual black wolfberry fruit (RBWF) is rich in nutrients and contains a diverse range of active substances, which may offer a viable alternative to antibiotics. This experiment was conducted to investigate the impact of varying levels of RBWF on the growth performance and rumen microorganisms of fattening sheep, and to quantify its economic benefits.MethodsIn this experiment, 40 three-month-old and male Duolang sheep with an average weight of 29.85 kg, selected for their propensity to gain weight, were randomly assigned to one of four groups, with ten sheep in each group. To this end, each group was fed with a different proportion of RBWF (0%, 2%, 5%, 8%), and rumen fluid samples were collected to detect differences in fermentation parameters and microbial structure.ResultsThe findings indicate that the dry matter intake, OM and NDF apparent digestibility of Duolang sheep in the H2 group were found to be significantly higher than those observed in the other groups (P < 0.05). The concentration of volatile fatty acids (VFAs), including acetate, propionate, iso-butyrate, butyrate and iso-valerate, in rumen fluid demonstrated a linear increase with the supplementation of RBWF in the diet (P < 0.05). The dominant bacteria in the rumen of Duolang sheep were identified as Prevotella, Christensenellaceae R7 group, NK4A214 group, Ruminococcus, and Rikenellaceae RC9 gut group. Compared with the CK group, the relative abundance of Prevotella, NK4A214 group, unclassified Prevotellaceae and Lachnospiraceae NK3A20 group in the rumen of sheep in each experimental group increased to varying degrees. The gross profit of the H2 group was significantly higher than that of the other groups.ConclusionIn conclusion, the supplementation of RBWF has been demonstrated to enhance the growth performance of Duolang sheep, optimise rumen fermentation parameters, and ultimately increase gross profit, of which 5 % is the best.